Postoperative Morbidity After Radical Resection of Retroperitoneal Solitary Fibrous Tumor - Zhuang, Aobo; Fang, Yuan; Ma, Lijie; Lu, Weiqi; Tong, Hanxing; Zhang, Yong (Frontiers in Surgery, 2022)
Background This study aimed to characterize the clinicopathological characteristics of retroperitoneal solitary fibrous tumor (RSFT) and analyze the safety of radical resection. Methods A retrospective analysis was conducted on the data of 32 RSFT patients who had undergone surgery with curative intent at the South Hospital of Zhongshan Hospital/Shanghai Public Health Clinical Center from February 2011 and June 2021. Results This cohort consisted of 16 (50%) male and 16 (50%) female patients, with the median age of all patients reaching 52 (ranging from 29 to 72) years. Tumor burden ranged from 3 to 25 (median, 10) cm, and 12 (38%) were classified to be malignant, while 20 (62%) were classified to be benign. 7 patients had undergone arterial embolization before surgery. 15 (47%) patients in total had undergone radiotherapy, 9 (28%) of which had undergone preoperative radiotherapy. Most of the patients (91%) achieved complete resection with median bleeding of 400 (ranging from 20 to 5000) ml. 9 (28%) patients had undergone packed red blood cell (RBC) transfusion, with a median of 5 (ranging from 2 to 10) U. For all patients, the 5-year progression-free survival rate and the overall survival rate respectively reached 75.8% and 80.0%. Adverse events were identified in 11 (34%) patients, and serious postoperative complications ( Clavien-Dindo≥3) were reported in 4 (12%) patients, of which 1 (3.1%) patient died after surgery. According to the univariate analysis, tumor burden (p=0.022), packed RBC transfusion (p=0.001) and postoperative hospital stay (0.027) were correlated with overall morbidity. As revealed by the multivariate analysis, packed RBC transfusion was an independent risk factor for postoperative morbidity (HR 381.652, 95% CI, 1.597-91213.029, p = 0.033). Conclusion RSFT was demonstrated as an uncommon, slow-growing and recurring tumor, with acceptable postoperative morbidity and mortality after surgical resection.